Circular economy and eco-innovations: a taxonomy of policy instruments - Campos, André Nunes de (2019)
Recently, amidst increasingly pressing environmental concerns, the Circular Economy (CE) concept has been defended, by both scholars and practitioners, as an alternative to the ‘take-make-dispose’ economic paradigm by emulating the naturally occurring, selfrenovating cycles. The CE is enabled by and depends on various technological and nontechnological eco-innovations (EIs), i.e., innovations that cause a net positive environmental impact. The complex and systemic interrelations and feedback mechanisms implicated have attracted attention to the role of innovation policy in driving EIs. However, the circular economy – eco-innovation – innovation policy nexus is only now beginning to emerge in academic literature and more research is needed to detail the instruments involved and understand their interplay towards promoting an EI-mediated CE transition. In the present work, we analysed data collected through systematic literature review to propose and characterise an evidence-based, goal-oriented taxonomy for policy instruments. Thus, six core categories of policy instruments are explored: 1) R&D increase, 2) Non-financial capabilities, 3) Network capability, 4) Increase demand, 5) Regulations and Standards, and 6) Foresight activities. Our results highlight the complexity underpinning the design of innovation policy mixes. We conclude that an approach that, on one hand, targets the various stages in material cycles and on the other hand, considers policy instrument features and their complementarity seems to benefit the creation of ‘circular’ innovations and the CE transition.